A review on novel COVID-19: background, etiology, pathogenesis, transmission, prevention and management - R, Kalyani.; Padmasri B.; Anilkumar V.; Prasanth. D. (Journal of Applied Pharmaceutical Research, 2020)
Mankind's history is watching a bizarre time battling an imperceptible adversary, the novel COVID-19 Coronavirus. At first seen in the Wuhan province of China, presently limitlessly spreading all over world. How the COVID 19 has been made on the globe become Pandemic needs no depiction. The virus has been accounted for affecting the lungs and related respiratory tracts promoting harm of the alveoli. It has been accounted that the respiratory sickness is the prevailing Clinical symptom of COVID-19. This review article discusses an easily understanding of the causes, different type of Human viruses regarded of Coronavirus, clinical diagnosis of RT-PCR, FET, Primary prevention and control of the virus. Therefore, this review article main theme is to provide more reliable and valid information to control and manage public emergency in both acute and chronic conditions of coronavirus